Do Ownership and Environment Affect Profits with the Role of the Independent Commissioners? - Noval, Muhammad; Rimayanti, Rimayanti; Malia, Malia; Syahid, Muhammad; Elzaanin, Amina A.A; Arumugam, Aswini (Al-Tijary, 2024)
This study aims to explore health company profits during the pandemic from the perspective of managerial ownership and environmental performance accompanied by the moderating role of independent commissioners. The use of Sharia-based health sector companies as companies that are very closely related to the pandemic events that occurred during the observation period of 2020-2021 resulted in 16 companies using quarterly reports, so there are 64 studio data. The data obtained was subjected to prerequisite tests using the classical assumption test, which was then tested by conducting F-test and t-test regression based on the hypotheses that had been developed. The study results prove that managerial ownership and environmental performance simultaneously increase profits. However, partially managerial ownership influences increasing profits, while environmental performance has no effect. The role of the independent board of commissioners has been proven to not influence managerial ownership and environmental performance in increasing the profits of Sharia companies in the health sector. This study implies that managerial ownership factors, environmental performance, and an independent board of commissioners play an essential role in increasing the profits of Sharia companies in the health sector, especially during the pandemic. The results can encourage strategic decision-making related to ownership structure and corporate governance to achieve sustainability and profitability.